DESAIN PERHITUNGAN BIAYA PRODUKSI UNTUK PERENCANAAN LABA PADA KOMODITI KOPI PERSIKLUS DI DESA SIPONJOT HUMBAHAS - Situmorang, Aston L.; Simanullang, Tuti Wilna (Jurnal Manajemen dan Bisnis, 2023)
Coffee is one of the important export commodities for the people of Indonesia which is able to contribute quite a large amount of foreign exchange. Siponjot Village, Lintong Nihuta District, is one of the villages that has a large potential for the development of Arabica coffee commodities because Siponjot village is the largest producer of Arabica coffee in Humbahas district. However, there are several obstacles faced in the development of coffee farming, including the calculation of production costs per cycle. Farmers do calculate costs, but it's limited to what costs they incur during production without calculating in detail the costs from land clearing to receiving the harvest, then they also don't know how much net income they get after deducting all costs, they also don't understand how calculate the break-even point and make a profit plan. This study aims to design the calculation of production costs for coffee commodities per cycle so that it is easier for farmers to find out the costs per cycle they incur and net income and then know the break-even point to make a bigger profit plan. This research was conducted in May-August 2022 in Lintong Nihuta District, Humbahas Regency, North Sumatra. The results of the study after calculating the production costs per cycle showed that in one coffee life cycle the farmers spent Rp. 551,368,400 with a yield of 29,940 kg and farmers experienced a profit of Rp. 346,831,600 per cycle.